The clinical study of personal hemodialysis treament to cardivascalar complication of diabetic kidney disease patients - XU Ye; HE Li-qun; DAI Si-si; ZHAO Jun; HUANG Ke; WANG Li-yong; WANG Jie; SHEN Xiao-qin (Linchuang shenzangbing zazhi)
Objective Exploring the clinical effects of personal hemodialysis to cardivascalar complication of diabetic kidney disease（DKD）,and inducing the incidence of cardiovascular events to improving the patient’s quality of life.Methods Choosing 50 DKD dialysis patients in our hospital from June 2013 to June 2014,all of the patients must be accorded with diagnostic standard of chronic kidney disease（CKD） and DKD.The diagnostic standards of CKD is glomerular filtration rate（GFR）less than 15 ml·min-1·（1.73 m2）-1.The diagnostic standards of DKD that is the GFR decreasing because of diabetic disease or albumin creatinine ratio（ACR） more than 30 mg/g.All of these diagnostic standards must up to three months.Those enrolled patients’ dialysis time should be up to three months and eliminate the other chronic disease result in kidney disease,enrolled patients who are make into two groups randomly.Treatment groups has 24 patients who are in personal hemodialysis,and the others are in regular hemodialysis,and then,comparing different month’sO,6,9,12) ultrasonic cardiogram and cardiovascular events before and after treatment Results（1）Before the treatment,two groups has no significantly different and statistical significance;（2） Comparing the treatment of pre and post,the ninth and twelveth month treatment group of left ventricle ejection fraction is better than before treatment After treated nine and twelve month later,the treatment group improving ejection fraction,left ventricular end diastolic diameter,left ventricular end systolic diameter better than matched group;（3）The rate of low blood pressure,heart failure,cardiac arrhythmia and myocardial infarction,ect much lower than matched group.Conclusions The personal hemodialysis can lower the DKD dialysis patients cardious complication and keep the heart structure steady by increasing LVEF,diastoling LVESd and LVEDd,that will inducing the incidence of heart symptoms and improving the dialysis patient’s quality of life,which is worth to be popularized.